Kulinaria w świadomości językowej Polaków, Rosjan i Niemców (aspekt aksjolingwistyczny) - Rodziewicz, Barbara (Studia Rossica Posnaniensia, 2018)
The article is an attempt at establishing a way of understanding the term Food in the systems of values in the language awareness of Poles, Russians and Germans. The author analyses the results of a Free Word Association Test.